EXAMINING THE EFFECT OF CONTEXTUAL TEACHING-LEARNING AND ANXIETY TOWARDS STUDENTS’ SPEAKING SKILLS - Suadiyatno, Taufik; Firman, Edi; Hanan, Ahmad; Sumarsono, Dedi (UNDIKMA Mataram (Eks. IKIP Mataram), 2020)
This research was aimed at finding out whether: (1) Contextual Teaching Learning has better effect than conventional method towards students speaking skill; (2) the students having low anxiety have better speaking skill than those who have high anxiety; and (3) there is an interaction between CTL and anxiety towards students speaking skill. This research was experimental study within quantitative approach. The total samples of this study were 66 students of tour and travel class of SMKN 2 Mataram that consist of two classes that determined by cluster random sampling technique. The instruments that were used to collect the data were test and questionnaire. The data was analyzed by using multifactor analysis of variance 2x2 and tuckey test. The result of this research revealed that the level of students anxiety that taught by CTL is lower than conventional, while students? speaking skill score that taught by contextual method was higher than conventional method. The level of anxiety has significant effect toward students? speaking skill. Therefore, it can be concluded that: 1) Contextual Teaching Learning method has better effect than Convetional method towards students speaking skill of the tour and travel students? class of SMKN 2 Mataram; 2) The students who have low speaking anxiety have better speaking skill than those who have high speaking anxiety at the tour and travel students? class of SMKN 2 Mataram; 3) There is an interaction between CTL and students? anxiety towards students speaking skill of the tour and travel students? class of SMKN 2 Mataram.